Digitalization Of Marketing And Human Resource Motivation On Economic Growth Of Kecamatan Parongpong Residents During The Pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine what factors can affect economic growth. The method used in this research is descriptive and verification methods. The head of the youth organization as many as 49 people became the population of this study. The test method used to test this research is a linear regression analysis with a determination coefficient of 5%. The results of the study indicate that the digitalization of marketing and human resource motivation has a significant effect on improving the economy in Kecamatan Parongponng partially or simultaneously. Digitalization of marketing and human resource motivation has an effect of 52.3%, while 47.7% is influenced by other factors.